(untitled) (Research, Society and Development, 2019)
The objective of this article is to present a study on transsexuality from the perspective of children’s play and how it affects the issue of social and self acceptance through cinematographic analysis and bibliographic studies. The concept of play based on Winnicott’s theories. It will raise questions about gender identity from the problematic brought by Judith Butler in conjunction with the definition of the gender roles attributed to definitive cultural constructions that are imposed in childhood and how this would apply in the experience of a transsexual child. It can be observed through the analysis of the scenes of the films: Tomboy (2011), Ma Vie En Rose (1997) and A Kid Like Jake (2018), each of which has as main theme a developing child oscillating among gender scripts. With exploratory research and a qualitative methodological approach, it was possible to conclude that play is directly related to the child’s play dimension, through which it ends up demonstrating how it understands the world around it. It is in this game that the child will identify himself and those around him, making the fantasy his way of expression.